Job design and job satisfaction: Empirical evidence for Germany? - René Fahr (Management Revue, 2011)
The present paper uses a large representative data set for Germany to analyze the effect of an enriched job design, which is characterized by a high degree of autonomy and multitasking, on job satisfaction. In our empirical approach we take job satisfaction as a proxy variable for workers' utility following the approach suggested in Clark/Oswald (1996). We present clear evidence that modern job design increases job satisfaction independent of worker characteristics and variations in the definition of enriched job design. We find some tentative evidence for the impact of the job design/ employee-match on job satisfaction. In particular, workers whose observable characteristics match the requirements of enriched workplaces report higher job satisfaction than workers who were mis-matched to enriched workplaces.
Keywords: J2; J28; M5; M54; 650; Human Resource Management practices; job satisfaction; job design; SOEP; autonomy; multitasking